Soil temperature change and its regional differences under different vegetation regions across China - Xiqiang Wang; Rensheng Chen; Chuntan Han; Yong Yang; Junfeng Liu; Zhangwen Liu; Shuhai Guo; Yaoxuan Song (International Journal of Climatology, 2021)
Changes in soil temperature will exert an important influence on the management and utilization of vegetation and agricultural production, whereas the spatiotemporal variations in soil temperature under different vegetation regions across China remain largely unknown. The shallow soil temperatures (0–20 cm) during the growing season (May–September) from 1965 to 2014 across China were analysed, and the findings showed that the spatial distribution of shallow soil temperature was determined primarily by latitude in eastern China (east of 110°E), and by altitude in western China (west of 110°E) with some high (low) temperature centres. The vegetation regions with relatively low soil temperatures are mainly concentrated in high altitude and high latitude areas, which have relatively large differences in soil temperature at different depths and relatively high soil warming rates. Over the past 50 years, shallow soil temperatures increased greatly during the growing season at the site, vegetation region and nation scales, but the warming rate and its relationship with climate change varied greatly. The soil temperature variables were affected substantially by air temperature and precipitation in the subtropical forest and tropical forest regions but were affected primarily by air temperature in the other vegetation regions. This difference may be due to the spatial difference in precipitation amounts across China, which affected the soil temperature via soil moisture feedback. Further study indicated that the warming rate in shallow soil was higher in stations (vegetation regions) with less precipitation than in those with more precipitation.